Edukasi Kunyit Asam Pereda Dismenorea - safitri safitri; Gustina Gustina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Dysmenorrhea is the medical term for menstrual cramps, which are caused by uterine contractions. The prevalence of dysmenorrhea in Indonesia reaches 98,8% in adolescents. Dysmenorrhea has a direct effect that has a negative impact on the quality of life of adolescents such as interfering with daily physical activities, school attendance, learning concentration and even academic achievement. Some teenagers who experience dysmenorrhea still use alternative therapies such as herbal medicine. Tamarind turmeric herbal medicine as a non-pharmacological method is safe and easy to obtain to treat dysmenorrhea and without side effects. Pondok Meja village has natural potential for developing turmeric cultivation. In the initial study, 70% of adolescent girls experienced dysmenorrhea, only 10% consumed the tamarind turmeric herbal to treat dysmenorrhea, and 80% of female adolescents did not know the benefits of tamarind turmeric in overcoming dysmenorrhea. Efforts that can be done are to to provide education about tamarind turmeric as a reliever of dysmenorrhea which aims to increase the knowledge of adolescent girls. This community service activity was carried out on 30 adolescent girls in Pondok Meja village from November to December 2021. The expected output target is to increase knowledge between before and after being given education. The method used is online education through zoom meeting and online education video that can be accessed via YouTube. Knowledge is assessed from the results of pretest and posttest through the google form. The result of this service is an increase in knowledge after being given online education through zoom meeting and online education video so that adolescent girls can consume tamarind turmeric drink as first aid in treating dysmenorrhea